The role of the LncRNA XIST/miR-15a-5p/MN1 signaling axis in gender disparities in bladder cancer prognosis - Cai, Fangzhen; Xu, Siwei; Li, Yinan; He, Qingliu; Su, Qingfu; Chen, Heyi; Liu, Weihui; Chen, Jiabi; Wang, Qingshui; Assaraf, Yehuda G.; Lin, Yao; Zhuang, Wei (Frontiers in Immunology, 2025)
BackgroundBladder cancer (BC) exhibits significant gender disparities in incidence and prognosis, with women experiencing worse prognosis despite lower incidence rates. This study aims to elucidate the molecular mechanisms underlying these gender-specific differences, focusing on the role of the long non-coding RNA XIST.MethodsComprehensive bioinformatics analysis was performed using TCGA and GSE13507 cohorts to identify gender-differential gene expression. Functional experiments including cell proliferation, migration, and invasion assays were conducted in bladder cancer cell lines. Molecular interactions were investigated through gene knockdown, overexpression, and luciferase reporter assays. A zebrafish model was employed to validate in vivo findings.ResultsOur study revealed that XIST expression is significantly higher in female bladder cancer tissues and strongly associated with poor prognosis in female patients. The XIST/miR-15a-5p/MN1/FZD2 signaling axis was found to play a critical role in promoting bladder cancer progression. Specifically, XIST upregulates MN1 by sponging miR-15a-5p, which in turn enhances FZD2 expression. Functional experiments demonstrated that XIST knockdown significantly inhibited bladder cancer cell proliferation, migration, and invasion, effects which could be reversed by FZD2 overexpression.ConclusionsThe XIST/miR-15a-5p/MN1 signaling axis plays a critical role in the gender disparity observed in bladder cancer prognosis, particularly in women. Targeting this pathway may offer new therapeutic strategies for improving outcomes in female BC patients.